THE ROLE OF LIBRARIES IN PROMOTING ADULT EDUCATION - Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article discusses the function of the library in the changing society and educational activity among elderly citizens. The growing number of elderly people in a society requires permanent revision and adaptation to the new conditions of education, social security, economy, health protection areas. Today the function of the library is seen as a multifunctional institution for education, leisure, culture, information and recreation. Modern library through participation in many programmes and projects provide elderly people with training in computer and digital skills, and functional literacy. Participation in library events enhances activity, engagement, participation in society`s life of the elderly.